Dysmenorrhea among students in Yaounde, Cameroon: associated factors and socio-cultural aspects - Fouedjio, Jeanne Hortence; Fouelifack, Florent Ymele; Fouogue, Jovanny Tsuala; Etame, Lionel; Fouelifa, Loic Dongmo; Mbu, Robinson Enow (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Dysmenorrhea is very common disorder. It affects the quality of life and is the main cause of school absenteeism’s among teenagers. The goal of this study was to determine socio-cultural aspects of dysmenorrhea among students in Yaounde and factors associated with it. Methods: Authors carried out a cross sectional analytic study in 2 secondary schools and a higher institute in Yaounde, from December 1, 2017 to June 30, 2018 (7 months). Authors included all students aged at least 15, in form 5 and above. In the higher institute, sampling was consecutive, while it was stratified into 2 clusters in the secondary schools. Odds ratios were determined to assess association between variables and P-value ˂0.05 was considered significant. Results: Of the 1059 participants, 800 had dysmenorrhea (prevalence: 75.5%). Mean age was 18.88±3.62 years (range: 15-45 years). Family history of dysmenorrhea (OR: 4.20 (95% CI: 3.02-5.83)) and stress ((OR: 2.16 (95% CI: 1.55 - 3.02)) were significantly associated with dysmenorrhea. A duration of menses ≤3 days was protective ((OR: 0.31 (95% CI: 0.12-0.82)). Dysmenorrhea remains a taboo for 23.6% of participants. Conclusions: Family history of dysmenorrhea and stress are risk factors for dysmenorrhea which remains a taboo for almost a fourth of affected women. Authors recommend educating women about dysmenorrhea and control psycho-social stress.